ANALISIS PENGELOLAAN WISATA BERBASIS SMART TOURISM DI DESA BANJARANYAR KECAMATAN BANJARANYAR KABUPATEN CIAMIS - Dicky; Kiki Endah; Arie Budiawan; Obang; Wasimin (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Tourism-based village development is an effort to find out and explore the tourism potential that exists in the village so that good management is needed to increase tourism development. Banjaranyar Village, Banjaranyar District, Ciamis Regency has potential sources of tourism that allow it to develop, including natural tourism, educational tourism and religious tourism. However, based on the results of observations, smart tourism-based tourism management in Banjaranyar Village, Banjaranyar District, Ciamis Regency is not yet optimal. This is caused by indicators including: 1) Management that is not conducive to educational tourism potential in Banjaranyar Village, Banjaranyar District, Ciamis Regency after the Covid-19 Pandemic, 2) Lack of optimal maintenance and damage to infrastructure to get to educational tourism locations in the Village. Banjaranyar, Banjaranyar District, Ciamis Regency, 3) There is an attitude from some local communities who do not fully support the development of educational tourism potential in Banjaranyar Village, Banjaranyar District, Ciamis Regency, 4) There are financial constraints that must be overcome by Banjaranyar Village, Banjaranyar District, Ciamis Regency.